Viral suppression in adolescents on antiretroviral treatment: review of the literature and critical appraisal of methodological challenges. Issue 3 (10th January 2016) - Ferrand, Rashida A.; Briggs, Datonye; Ferguson, Jane; Penazzato, Martina; Armstrong, Alice; MacPherson, Peter; Ross, David A.; Kranzer, Katharina
Abstract: Objective: Medication adherence is often suboptimal for adolescents with HIV, and establishing correct weight‐based antiretroviral therapy dosing is difficult, contributing to virological failure. This review aimed to determine the proportion of adolescents achieving virological suppression after initiating ART. Methods: MEDLINE, EMBASE and Web of Science databases were searched. Studies published between January 2004 and September 2014 including ≥50 adolescents taking ART and reporting on the proportion of virological suppressed participants were included. Results: From a total of 5316 potentially relevant citations, 20 studies were included. Only eight studies reported the proportion of adolescents that were virologically suppressed at a specified time point. The proportion of adolescents with virological suppression at 12 months ranged from 27 to 89%. Conclusion: Adolescent achievement of HIV virological suppression was highly variable. Improved reporting of virological outcomes from a wider range of settings is required to support efforts to improve HIV care and treatment for adolescents.